The study of chemical modifications on the properties of soy protein isolate (SPI) / kapok husk (KH) biocomposite films for agriculture applications / \c Ramyah Kalai Chelvie A/P Pani Sellivam. - Pani Sellivam, Ramyah Kalai Chelvie (School of Materials Engineering, Universiti Malaysia Perlis, 2018)
The aims of research to investigate the effect of kapok husk as reinforcement in soy protein isolate biocomposites film. The objectives of research are ; to study the effect of KH loading on tensile properties, morphology, thermal properties, FTIR, moisture content, total soluble matter, gel fraction and biodegradation properties of SPI/KH biocomposite films ; to investigate the effect of different types of crosslink agent, such as phthalic anhydride (PA), adipic acid (AA) and formaldehyde (FA) on properties of SPI/KH biocomposite films ; to study the effect of surfacemodification of KH with 2-ethylhexyl acrylate (EA), sodium dodecyl sulfate (SDS) and methyl methacrylate (MMA) on properties of SPI/KH biocomposite films.